Electrical Rate Policy during the Dictatorship. Lisbon and Oporto (1936-1974) - Bussola, Diego (2006)
The aim of this paper is to contribute to today’s discussion on Government’s implication on electrical rate systems. We show the progressive centralization in the regulation of electric rates that was in force during the ‘Estado Novo’ and the effects of certain policies that produced different lifestyles, in what regards the use of energy in the two main Portuguese cities (Lisbon and Oporto). Finally, we explain why, from the demand point of view, today’s electrical rate system (used since the nationalisation, c.1975) isn’t more “social”, as it was announced, than the former regressive rate system used during ‘Salazarism’.